Economic values of wetlands conservation from the perspective of urban non-users - Othman, Jamal; Asmuni, Shahariah (Universiti Utara Malaysia, 2003)
Benefits of wetlands resources that are tradable in the market, for example, wood products and fish are readily observable through market prices. However, non-marketable benefits such as the preservation of environmental functions and ecosystems are less objective. This study applies the Dichotomous- Choice Contingent Valuation Method on the Paya Indah wetlands in Kuala Langat, Selangor to estimate the non-marketed benefits of conserving the wetland from the perspective of non-users, in particular among urban households in Selangor. Results indicate that the mean willingness to pay (equivalent surplus) which reflects the non-use values of Paya Indah wetlands accrued to urban non-user households in Selangor ranges from RM28 - RM31 annually. The large sum of monetary value that households place in the conservation of Paya Indah illustrates partially the magnitude of social benefits that society at large obtains from the assurance that the wetland is to be maintained as a site for nature conservation. This strongly indicates that conservation of the wetlands is highly valued by the general public.